2007
DOI: 10.1111/j.1528-1167.2007.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Provoked Ictal SPECT and Depth Recordings in Adult Drug‐Resistant Epilepsy Patients

Abstract: Summary:Purpose: To correlate ictal hyperperfusion singlephoton emission computed tomography (SPECT) area during provoked seizures to the epileptogenic zone (EZ), as defined by depth recordings in adult drug-resistant patients.Methods: We included in the study eight drug-resistant epilepsy patients, subjected to both noninvasive and invasive (stereo-electroencephalography, SEEG) presurgical evaluation in the Epilepsy Surgery Center of the Catholic University in Rome, from 2001 to 2003. All patients were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…It is generally assumed that a decrease in seizure threshold is a hallmark of epileptogenesis [47], indicating cortical hyperexcitability, but seizure threshold is difficult to assess in humans. However, Barba et al [48,49] used PTZ to provoke seizures during presurgical evaluation in patients with intractable epilepsy and reported that PTZ is safe for this purpose. An alternative method of determining alterations in brain excitability following brain insults in both animal models and patients is cortical excitability measures on transcranial magnetic stimulation (TMS) [50][51][52].…”
Section: Discussionmentioning
confidence: 98%
“…It is generally assumed that a decrease in seizure threshold is a hallmark of epileptogenesis [47], indicating cortical hyperexcitability, but seizure threshold is difficult to assess in humans. However, Barba et al [48,49] used PTZ to provoke seizures during presurgical evaluation in patients with intractable epilepsy and reported that PTZ is safe for this purpose. An alternative method of determining alterations in brain excitability following brain insults in both animal models and patients is cortical excitability measures on transcranial magnetic stimulation (TMS) [50][51][52].…”
Section: Discussionmentioning
confidence: 98%
“…23 Therefore, it may be concluded that temporal neocortical spikes with maximum mesial responses are indeed dependent on a more intense neuronal discharge in mesial temporal structures. In the third patient with MTS with a neocortical activation, we could infer that the main epileptogenicity was neocortical and not mesial.…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients with electrophysiologic-verified epileptogenic lesions, such as HS or other focal pathology, some do not benefit from surgery. Other patients who fail surgery may in fact have temporal plus epilepsy, with an epileptogenic network that extends into other cerebral lobes (Barba et al, 2007; Bertram, 2009). Ictal SPECT scans in MTLE show an increase in tracer uptake in the medial temporal region, cerebellum, thalamus, insula, and putamen.…”
Section: Single-photon Emission Computed Tomographymentioning
confidence: 99%